Psychometric properties and item response theory analysis of the Persian version of the social pain questionnaire - Sepehrinia, Mahya; Farahani, Hojjatollah; Watson, Peter; Amini, Nasim (Frontiers in Psychology, 2024)
Introduction Social pain is an emotional reaction which is triggered by social exclusion and has been extensively investigated in the literature. The Social Pain Questionnaire (SPQ) is a self-report instrument which is the only scale for measuring social pain as a dispositional factor. The current study aimed at examining the psychometric properties of the SPQ in an Iranian sample. Materials and methods A sample of participants (N = 400) was recruited in a cross-sectional validation study. Exploratory Factor Analysis (EFA) as well as Confirmatory Factor Analysis (CFA) were conducted. The Item Response Theory (IRT) model parameters were evaluated and item response category curves were presented. Convergent and divergent validities as well as the reliability (by using Cronbach’s alpha coefficient) were also assessed. Results The SPQ’s unidimensionality was affirmed (RMSEA = 0.078; CFI = 0.915; TLI = 0.99) and its internal consistency was robust (Cronbach’s α = 0.94). The correlation between the SPQ and the following measures endorsed its divergent and convergent validity: Self-esteem (r = −0.424), Perceived Social Support (r = −0.161), and Interpersonal Sensitivity (r = 0.636). Finally, Item Response Theory Analysis emphasized the effectiveness of the SPQ items in discerning various levels of social pain. The theta level ranged between −1 and + 1.2 and the IRT-based marginal reliability was 0.92 for the total score. Discussion The Persian SPQ stands as a reliable and valid measure for evaluating social pain. This scale has the potential to stimulate further research in the field for both clinical and non-clinical settings. Conclusion By employing Item Response Theory (IRT) analysis, we have transcended the theoretical psychometric evaluation of the SPQ scale and demonstrated that SPQ is a unidimensional, valid and reliable measurement tool.